The Relevance of SDGs and Islamic Legal Principles in Divorce Cases to Judicial Reasoning - Lukman Yafi; Shikdar Mohammad Riazul (Walidem Institute and Publishing (WIP), 2025)
This study investigates the relevance of the Sustainable Development Goals (SDGs) and Islamic legal principles in shaping judicial reasoning in divorce by ṭalāq cases, with empirical attention directed toward a decision from the Selangor, Malaysia Religious Court. Objective: The primary objective is to examine how judicial reasoning incorporates Islamic legal norms, statutory requirements, and SDG commitments—particularly SDG 5 (Gender Equality), SDG 16 (Peace, Justice, and Strong Institutions), and SDG 10 (Reduced Inequalities)—in ensuring procedural justice, fairness, and the protection of vulnerable parties in family law disputes. Theoretical framework: The analysis draws upon Islamic family law, emphasizing maṣlaḥah, justice, and judicial discretion, combined with legal positivism and socio-legal jurisprudence. This framework allows for understanding how judges interpret textual provisions while simultaneously addressing broader social objectives aligned with the SDGs. Literature review: Existing scholarship highlights the significance of judicial discretion in Islamic family law, the evolving social dimensions of divorce litigation, and the tension between formal rules and contextual considerations. However, limited research explicitly addresses the integration of SDG principles into judicial reasoning in Muslim-majority jurisdictions, revealing a gap that this study seeks to fill by linking global development commitments with Islamic judicial practice. Method: Using a qualitative descriptive design, the study analyzes primary data derived from judicial interviews and official court documents, supported by secondary materials such as statutory instruments, Islamic legal texts, and contemporary academic literature. Results: The findings show that judges in Selangor apply a balanced approach that upholds procedural legality while considering the psychological, economic, and social welfare of both spouses. Judicial reasoning demonstrates sensitivity to gender equality, equitable access to justice, and family well-being—aligning implicitly with SDGs—while firmly grounded in Islamic legal principles. The decision-making process reflects harmonization between legal certainty, maṣlaḥah, and the pursuit of substantive justice. Implications: The study offers practical insights for policymakers, legal practitioners, and scholars seeking to integrate SDG-aligned values into Islamic family law jurisprudence. Novelty: Its key contribution lies in articulating how SDG commitments and Islamic legal principles converge within judicial reasoning, offering a new analytical lens for understanding contemporary divorce adjudication in Muslim legal systems.